The incidence of Nasopharyngeal Carcinoma in Pahang state of Malaysia from 2012 to 2017 - Ahmad, Azmir; Mohd Yassin, Wardah; A. Rahman, Nor Azlina; Leman, Wan Ishlah; Rosla, Luqman; Paul, Mark; Syed Yussof, Sharifah Nor Ezura; Mohamed@Awang, Kamariah; Abdullah, Kahairi; Kaderi, Mohd Arifin (Penerbit Universiti Sains Malaysia, 2021)
Background: Nasopharyngeal carcinoma (NPC) is the fifth most common cancer among Malaysians. While several studies have reported the trend of NPC in other states in Malaysia, no studies have reported the trend of NPC in Pahang state. This study was designed to report the number and distribution of newly diagnosed NPC cases in Pahang. Methods: NPC cases that were diagnosed between 2012 and 2017 in two referral hospitals in Pahang were traced. The crude incidence rate (CR) and age-standardised rate (ASR) were calculated to investigate the NPC incidence. Results: There were 143 new cases of NPC reported from the two hospitals. The mean age at diagnosis was 52.0 ± 13.7 years old. The majority of cases involved males (74.1%) with a male to female ratio of 2.9:1. Chinese males were found to have the highest incidence with a mean ASR of 4.7 per 100,000 population. Overall, the mean ASR for Pahang was 2.4 per 100,000 population for males and 0.9 per 100,000 population for females. Conclusion: The total number of NPC cases reveals an increasing trend from 2012 to 2014 and then a slightly decreasing trend from 2015 to 2017. The incidence of NPC in Pahang was intermediate in males and low in females.